2022
DOI: 10.3390/agronomy12102309
|View full text |Cite
|
Sign up to set email alerts
|

Chorisia speciosa Extract Induces Systemic Resistance against Tomato Root Rot Disease Caused by Rhizoctonia solani

Abstract: Chemical pesticides and fungicides are used extensively, negatively affecting people’s health and the environment. Reducing synthetic pesticides and increasing the efficiency of sustainable food production using plant extracts as natural chemicals is a win–win. Here, we first describe and evaluate an ethanolic extract of Chorisia speciosa for its protective and curative activities against Rhizoctonia solani in greenhouse-grown tomato plants. The results showed that the mycelial growth of R. solani was complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Meanwhile, Tralamazza et al [15] have reported that this species complex is associated with panicle infection in wild rice in Brazil. Numerous research studies have explored the effectiveness of different extracts against R. solani, revealing encouraging outcomes regarding their antifungal properties [16][17][18]. Antifungal properties towards the fungi Aspergillus flavus, Candida spp., and A. niger were detected using water, alcohol, ether, and chloroform-derived extracts of S. macrophylla leaves [19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Tralamazza et al [15] have reported that this species complex is associated with panicle infection in wild rice in Brazil. Numerous research studies have explored the effectiveness of different extracts against R. solani, revealing encouraging outcomes regarding their antifungal properties [16][17][18]. Antifungal properties towards the fungi Aspergillus flavus, Candida spp., and A. niger were detected using water, alcohol, ether, and chloroform-derived extracts of S. macrophylla leaves [19].…”
Section: Introductionmentioning
confidence: 99%